The Gd2O3 – GdSrFeO4 pseudo -binary phase diagram - K.M. Kenges; A.A. Krasilin; Е.А. Тugova (Heliyon, 2024)
The Gd2O3 – GdSrFeO4 pseudo-binary phase diagram is presented for the first time. The liquidus and eutectic temperatures, metatectic points of the Gd2O3 transformations in the Gd2O3 – GdSrFeO4 section were defined using the Schröder–Le Chatelier equation, neglecting the effect of the isobaric heat capacity. The calculations were based on experimental data on the melting points of the end-members and the eutectic composition. From the results of phase relationships studies (subsolidus and high temperature region including literature data as well) and the above approach the Gd2O3–GdSrFeO4 pseudo-binary phase diagram in the temperature range 1400–2410 °C in air was constructed.It was shown that GdSrFeO4 of the K2NiF4- type is stable from 1100°С to a congruent melting temperature of 1560°С in air. The Gd2O3 – GdSrFeO4 system is eutectic with no intermediate compounds.